2006
DOI: 10.1063/1.2172411
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a radiation resistant, high efficiency SiC betavoltaic

Abstract: A SiC p-i-n junction betavoltaic was fabricated, and electrical power output under irradiation from an 8.5GBq P33 source was monitored over a period of four half-lives of the radioisotope. The open-circuit voltage (VOC) of the device was 2.04±0.02V, and the peak power (Pout) was 0.58±0.02μW (2.1±0.2μW∕cm2) at 1.60V. The conversion efficiency (ηconv) was 4.5%±0.3% and the normalized power output indicates no device degradation over more than 3months (four half-lives of the source).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(62 citation statements)
references
References 5 publications
1
55
0
3
Order By: Relevance
“…The energy conversion efficiency is found to be about 0.1%. This is comparable to other reported betavoltaic devices powered by tritium 2,4 and less than that of the recently reported SiC pn-junction cell using high energy betas from 63 Ni and 33 P. 5,6 In the gaseous CPD cells, the low-power density and conversion efficiency is attributed to the relatively high ionization energy, while in the a-Si: H CPD cells, the lower performance is attributed to the low built-in field and associated higher recombination rate.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The energy conversion efficiency is found to be about 0.1%. This is comparable to other reported betavoltaic devices powered by tritium 2,4 and less than that of the recently reported SiC pn-junction cell using high energy betas from 63 Ni and 33 P. 5,6 In the gaseous CPD cells, the low-power density and conversion efficiency is attributed to the relatively high ionization energy, while in the a-Si: H CPD cells, the lower performance is attributed to the low built-in field and associated higher recombination rate.…”
supporting
confidence: 69%
“…[1][2][3][4][5][6] A number of nuclear-toelectrical energy conversion integrations, which had been investigated previously, are receiving renewed attention and novel materials and modern microfabrication techniques are being introduced. 1, 3 In recent years, a series of studies have been reported on betavoltaics employing semiconductor pn junction using materials such as amorphous silicon, 2 porous silicon, 4 silicon carbide, 5,6 and gallium arsenide/nitride. 1 The efficiency and longevity of these battery structures rely on high-quality pn junctions, which are often susceptible to radiation damage and lack structural self-healing resiliency.…”
mentioning
confidence: 99%
“…Another material that can be used as converter material is SiC; Chandrashekhar et al proved a 63 Ni-SiC microbattery with at least 6% efficiency, 14 whilst Eiting et alp r o v e da 33 P-SiC microbattery with 4.5% efficiency. 15 Bormashov et al 6 reported a 63 Ni-diamond betavoltaic microbattery and a 238 Pu-diamond alpha-voltaic microbattery with conversion efficiencies as high as 0.6% and 3.6%, respectively, at room temperature. A rapid degradation in the alpha battery was observed due to radiation induced defect creation caused by the high-energy particles.…”
Section: B Beta-and Alpha-voltaic Microbatteriesmentioning
confidence: 99%
“…Wang et al [4] demonstrated a 63 Ni-GaAs microbattery with 0.075% conversion efficiency at 20 °C; while Butera et al [5] proved a 63 Ni-GaAs cell with internal conversion efficiencies of 11% and 22% at 20 °C and at -20 °C, respectively. Chandrashekhar et al reported a 63 Ni-SiC microbattery with at least 6% efficiency [6], whilst Eiting et al a 33 P-SiC microbattery with 4.5% efficiency [7] at room temperature. Cheng et al [8] investigated a high open circuit voltage (1.64 V) 63 Ni-GaN beta-voltaic microbattery with a conversion efficiency of 0.98% at room temperature; while Bormashov et al [9] proved a 63 Ni-diamond betavoltaic microbattery with conversion efficiencies as high as 0.6% at room temperature.…”
Section: Introductionmentioning
confidence: 99%